Rethinking 'Method' in Early Childhood Writing Education - Hermansson, Carina; Saar, Tomas; Olin-Scheller, Christina (Educare, 2014)
This article describes how the process of writing a fictional narrative, “My Story”, transforms and emerges over a period of five days in a Swedish early childhood classroom. Our purpose is to explore and describe how this method-driven writing project emerge in relation to material and discursive conditions, and to provide an empirically based understanding of the forces, flows and processes at work. This entails understanding processes of writing as an effect of complex relationships between the individual (the teacher and the student), the learning outcome, the affect, the talk, the motion, the body and the material. The results show how the writing project on some occasions come to a stop, sometimes take new directions or activate unforeseen affects and open for new becomings. The article also discusses how methods on the one hand has an explicit and formalized side, possible to articulate and predict. But on the other hand, is embedded in and driven by affects that changes both the method, the text production and the writing-learning subject. The article ends with a discussion of implications and possibilities understanding teaching methods of writing as dynamic processes that continually open for a variety of assemblages, flows and forces